English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Find the value of each of the following polynomials for the given value of the variable. -x^2-5x-6 , x=-3 and x=-2

2007-09-08 02:32:53 · 3 answers · asked by Anonymous in Science & Mathematics Mathematics

3 answers

Factor:
- x^2 - 5x - 6 = 0
(x + 3)(- x - 2) = 0

1st x:
x + 3 = 0
x = - 3

2nd x:
- x - 2 = 0
- x = 2
x = - 2

Answer: x = -3, x = - 2

Proof (x = - 3):
- (- 3)^2 - 5(- 3) - 6 = 0
- (9) + 15 - 6 = 0
- 9 + 9 = 0

Proof (x = - 2):
- (- 2)^2 - 5(- 2) - 6 = 0
- (4) + 10 - 6 = 0
- 4 + 4 = 0

2007-09-11 20:32:46 · answer #1 · answered by Jun Agruda 7 · 3 0

in effortless terms rewrite the equation, changing each and every and each x with its somewhat value and calculating the function value. I surely have rewritten the subject rely concerns for you. All you ought to do are the calculations. A: f(-3) = (-3)³+5(-3)²-7(-3)-8 B: f(0) = (0)³+5(0)²-7(0)-8 C: f(2) = (2)³+5(2)²-7(2)-8

2016-12-16 14:41:28 · answer #2 · answered by jowers 4 · 0 0

For x = -3 ---> -(-3)^2-5(-3)-6 = -9 +15 -6 = 0

-x^2-5x-6 = (-x - 3)(x + 2) ???????

2007-09-08 02:58:07 · answer #3 · answered by Will 4 · 0 0

fedest.com, questions and answers